ACCOUNTING IN THE STABILIZATION PROGRAM. - Green, Paul M. (The Accounting Review, 1945)
Abstract The U.S. Office of Price Administration (OPA) has had an assignment generally unique in American economic activity. It has been given the responsibility for price control, rent control, and rationing, three activities that were not customary for the American people. In some form OPA affects practically every person in the nation. Its programs have required a large amount of accounting work, and just as these programs of price control, rent control, and rationing were new to the average citizen, the great use to which accounting had to be put was new to both industry and government. The purpose of this article is to set forth the manner in which accounting is used within OPA and to show its place in the over-all program of the agency. In establishing wartime controls in fields where the American people had never before had such controls, it was necessary to set up an organization that would be flexible enough to permit efficient operation in the face of a rapidly developing emergency. To obtain such an organization, a staff that would combine a wide range of training and experience had to be recruited. Business specialists from industry, specialists in industrial research and economics, lawyers, accountants, and other specialists were called on to cooperate in this new undertaking.